The Working Mind Meaning and Mental Attention in Human Development - Pascual-Leone, Juan (The MIT Press, 2021)
A general organismic-causal theory that explicates working memory and executive function developmentally, clarifying the nature of human intelligence. In The Working Mind, Juan Pascual-Leone and Janice M. Johnson propose a general organismic-causal theory that explicates working memory and executive function developmentally and by doing so clarifies the nature of human intelligence. Pascual-Leone and Johnson explain "from within" (that is, from a subject's own processing perspective) cognitive developmental stages of growth, describing key causal factors that can account for the emergence of the working mind as a functional totality. Among these factors is a maturationally growing mental attention. After reviewing meaning-driven processes and constructivist knowledge principles that underlie what Pascual-Leone and Johnson term their Theory of Constructive Operators (TCO), they propose the TCO as as a developmental and neuropsychological approach to human cognitive and affective processes and their development. They present a novel method of mental task analysis that generates from-within process models of subjects' attempts to solve specific tasks. They provide an interpretation of brain semiotic processes that deploys TCO in functionally distinct brain locations. Finally, they show how TCO explicates complex human issues including consciousness, the self, the will, motivation, and individual differences, with applications in education, psychotherapy, and cognitive neuropsychology.